ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR CPO (BAHAN BAKU MINYAK GORENG) INDONESIA PADA TAHUN 1973 - 1998 - Wahyu, Wahyu; Triyono, Triyono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
The demand for cooking oil from domestic and foreign market has madetrade of CPO as cooking oil raw material. The strength of CPO trade iscaused by amount of government wish to keep cooking oil price stability asdomestic main need and by the amount of government interest to increaseforeign exchange achievement. The research is centered on variables whichinfluence on the number of CPO export from Indonesia. The data used aretime series data from 1973-1988 which is taken from BPS (Central Bureauof Statistic) of Indonesian Plantation Annual Report. Whereas analysismethod used are Double Linear Regression by using OLS (Method ofOrdinary Least Squares) with variables test toward classical assumption andstatistic test.